Transformational Leadership and its Impact on School Climate and Teachers’ Self-Efficacy in Indonesian High Schools - Damanik, Enceria; Aldridge, Jill (Rowman & Littlefield, 2017)
This study examined the relationships between principals’ leadership, school climate, and teachers’ sense of self-efficacy. Drawing on existing scales, this study examined six aspects of principal leadership (professional interaction, participatory decision-making, individual support, intellectual stimulation and moral perspective) and four school climate factors (staff collegiality, goal consensus, work pressure, resource adequacy, and staff freedom). The participants included 604 Indonesian teachers drawn from 27 high schools. The data were analysed using Structural Equation Modeling. The results indicated statistically significant and positive relationships between leadership style, school climate, and teacher self-efficacy. With the exception of individual support, the relationships between principal leadership and teacher self-efficacy were largely indirect, mediated through staff collegiality and goal consensus.